Evolutionary dynamics of 5S rDNA location in acridid grasshoppers and its relationship with H3 histone gene and 45S rDNA location - Cabral-de-Mello, Diogo C. [UNESP]; Cabrero, Josefa; López-León, María Dolores; Camacho, Juan Pedro M. (Springer Nature, 2011)
We analyze the chromosomal location of 5S rDNA clusters in 29 species of grasshoppers belonging to the family Acrididae. There was extensive variation among species for the number and location of 5S rDNA sites. Out of 148 sites detected, 75% were proximally located, 21.6% were interstitial, and only 3.4% were distal. The number of 5S rDNA sites per species varied from a single chromosome pair (in six species) to all chromosome pairs (in five species), with a range of intermediate situations. Thirteen chromosomes from eight species carried two 5S rDNA clusters. At intraspecific level, differences among populations were detected in Eyprepocnemis plorans, and some heteromorphisms have also been observed in some species. Double FISH for 5S rDNA and H3 histone gene DNA, performed on 17 of these 29 species, revealed that both markers are sometimes placed in a same chromosome but at different location, whereas they appeared to co-localize in five species (Calliptamus barbarus, Heteracris adpersa, Aiolopus strepens, Oedipoda charpentieri and O. coerulescens). Double fiber-FISH in A. strepens and O. coerulescens showed that the two DNAs are closely interspersed with variable relative amounts of both classes of DNA. Finally, no correlation was observed between the number of 5S and 45S rDNA clusters in 23 species where this information was available. These results are discussed in the light of possible mechanisms of spread that led to the extensive variation in the number of clusters observed for both rDNA types in acridid grasshoppers. © 2011 Springer Science+Business Media B.V.
Keywords: Fluorescence in situ hybridization; Grasshopper; Histone genes; Multigene families; rDNA; histone; ribosome DNA; ribosome RNA; RNA 5S; RNA, ribosomal, 45S; animal; Caelifera; chromosome map; cytology; evolution; fluorescence in situ hybridization; genetics; Greece; karyotyping; male; methodology; Morocco; multigene family; Spain; species difference; Animals; Biological Evolution; Chromosome Mapping; DNA, Ribosomal; Grasshoppers; Histones; In Situ Hybridization, Fluorescence; Karyotyping; Male; Multigene Family; RNA, Ribosomal; RNA, Ribosomal, 5S; Species Specificity; Acrididae; Aiolopus; Calliptamus barbarus; Eyprepocnemis plorans; Oedipoda